Migrants shaping Europe, past and present : multilingual literatures, arts, and cultures - Solterer, Helen; Joos, Vincent (Manchester University Press, 2022)
This comparative collection makes the case for the sustained contribution of migrants to European literatures, arts and social cultures, in early modern times and today. Iberia/Maghreb, Sicily/Lampedusa and Calais provide key examples for composing this new chapter in cultural history.